2018
DOI: 10.1080/15287394.2018.1504702
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive outcomes in rat female offspring from male rats co-exposed to rosuvastatin and ascorbic acid during pre-puberty

Abstract: Dyslipidemias are occurring earlier in different countries due to the increase of obesity, bad eating habits, and sedentary lifestyle. Rosuvastatin reduces serum cholesterol; however, several studies associated statin exposure with male reproduction impairment. Ascorbic acid (AA) is an antioxidant substance that plays a protective role in the male reproductive system. Male rats were randomly divided into 6 experimental groups (n = 10), which received saline solution 0.9%, 3 or 10 mg/kg/day of rosuvastatin, 150… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…The results have been promising, with a study concluding that a grape seed extract and atorvastatin combination treatment showed a noticeable increase in serum testosterone and sperm count whilst reducing levels of superoxide dismutase, caspase, and glutathione. Some studies have also shown the enhanced effects of antioxidants given alongside a statin with the antioxidants’ ability to diminish the statins’ adverse effects [ 92 ]. Conversely, one study showed the dose-dependent antioxidant and anti-apoptotic properties of rosuvastatin on diabetes-induced reproductive damage [ 43 ].…”
Section: Addressing the Problem: Should Antioxidants Be Administered ...mentioning
confidence: 99%
“…The results have been promising, with a study concluding that a grape seed extract and atorvastatin combination treatment showed a noticeable increase in serum testosterone and sperm count whilst reducing levels of superoxide dismutase, caspase, and glutathione. Some studies have also shown the enhanced effects of antioxidants given alongside a statin with the antioxidants’ ability to diminish the statins’ adverse effects [ 92 ]. Conversely, one study showed the dose-dependent antioxidant and anti-apoptotic properties of rosuvastatin on diabetes-induced reproductive damage [ 43 ].…”
Section: Addressing the Problem: Should Antioxidants Be Administered ...mentioning
confidence: 99%
“…The rosuvastatin doses chosen for this study are based on the lowest and highest doses applied in human therapy for children ( Leite et al, 2018a , Leite et al, 2019b , Leite et al, 2018c ), adapted for rodents considering their body surface area, as proposed for Reagan-Shaw et al ( Reagan‐Shaw et al, 2008 ).…”
Section: Methodsmentioning
confidence: 99%
“…Rosuvastatin can delay pubertal development, reduce sperm quality, impair spermatogenesis, and alter hormonal signaling ( Leite et al, 2014 , Leite et al, 2018a , Leite et al, 2019b ). Also, rosuvastatin exposure in male rats might affect reproductive function in an intergenerational manner, by damaging ovarian and uterine histophysiology of female offspring ( Leite et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dados mais recentes publicados por nosso Laboratório indicam que a exposição à rosuvastatina em ratos durante a peri-puberdade tem potencial para alterar parâmetros reprodutivos de forma transgeracional, já que a prole masculina desses ratos apresenta aumento na fragmentação de DNA espermático, depleção androgênica, alterações estruturais nos testículos e epidídimos, além de prejuízos à qualidade espermática . A prole feminina, por sua vez, também mostra alterações na função reprodutiva, evidenciada pela diminuição da contagem de corpos lúteos nos ovários, além de alterações histomorfométricas no epitélio luminal uterino e desregulação dos níveis de LH durante a puberdade (Leite et al, 2018c).…”
Section: Efeitos Das Estatinas Sobre a Função Reprodutivaunclassified
“…Rosuvastatin is able to delay pubertal development, reduce sperm quality, impair spermatogenesis and alter hormonal signaling [13][14][15]. Also, rosuvastatin exposure in male rats might affect reproductive function in an intergeneration manner, by damaging ovarian and uterine histophysiology of female offspring [16].…”
Section: Short-and Long-term Effects On Reproductive Parameters Of Fe...mentioning
confidence: 99%